Bank Indonesia's Strategy in Accelerating Sharia Economic Growth - Said, Ahmad; Susanto, Eko (Journal of Islamic Economy, 2024)
Seconomy has become an integral part of the Indonesian economic system, especially after the implementation of policies that support the sustainability of this sector. In an effort to accelerate the growth of the sharia economy, Bank Indonesia (BI) plays an important role with various strategic policies implemented to strengthen this sector. The strategies implemented by BI not only include monetary policy, but also financial inclusion, development of the sharia capital market, and strengthening of sharia financial institutions. This study aims to explore more deeply the efforts of Bank Indonesia in encouraging the development of the sharia economy and its impact on overall economic growth. The research method used in this study is a qualitative descriptive approach with analysis of literature studies and relevant secondary data. Based on the analysis conducted, the strategies implemented by Bank Indonesia have proven effective in increasing the contribution of the sharia economy sector to Indonesia's Gross Domestic Product (GDP). Bank Indonesia, through comprehensive policies, provides significant impetus for the growth of the sharia economy, both in terms of macroeconomic policies and the real sector.